PERAN DIGITAL MARKETING TERHADAP PENGEMBANGAN UMKM KERIPIK TAHU DI DESA LEUWEUNG KOLOT RW 04 - Ade Hendri Hendrawan; Berlina Wulandari; Dewi Primasari; Rifa Syafira; Neng Siti Najiah; M. Adam Rizky Zidan S; Zaini Adam Dzikrillah; Pefry Praguntara (JPMUJ, 2025)
As a result of offline transactions becoming it will be easier for UMKM participants to complete transactions. Digital technology has a significant disadvantage compared to UMKM. Emerging technology uses the more powerful and long-lasting potential of UMKM. Social media and online shopping can help UMKM entrepreneurs make money. It is understood that UMKM students have not actively participated in digital growth, particularly due to their limited understanding of digital marketing. The goal of the community outreach program at UMKM Desa Leuweung Kolot is to provide digital marketing training as a means of generating revenue and as a requirement for any technology-based marketing network.